The Consistency of Charitable Behaviour and Its Fund Raising Implications - Kuti, Éva (Competitio, 2008)
This paper tries to take an initial step toward a deeper understanding of the differences and similarities between corporate, individual and 1% philanthropy. Though both corporate and individual giving havea huge international literature (e.g. Adam 2004; Archambault & Boumendi 1998; Burlingame 1997, 2001; Halfpenny 1999; Schervish & Haven, 1997; Wang & Graddy 2008; Zamagni,1995) and 1% philanthropy is also discussed by several, mainly Eastern European authors (e.g. Bódi 2001; Chano 2008; Gerencsér & Oprics 2007; Török & Moss 2004; Vajda & Kuti 2002), the connections between these different kinds of philanthropic activities have not yet been scrutinized. Correspondingly, very little attention has been paid to the issues of how third sector organizations could develop an efficient ‘fund raising mix’; how they should combine their efforts to solicit contributions from different kinds of donors. In order to answer these questions, the author takes an interdisciplinary approach; she uses several different types of analytical and statistical methods. The statistical analysis of the donors’ motivation is based on the results of three empirical surveys of individual giving, 1% philanthropy and corporate donations which were carried out in Hungary over the last couple of years. The third sector organizations’ fund raising behaviour is analyzed using both official statistical data (KSH 1998–2008) and information gathered through interviews (Laki & Szalai 2004; T. Puskás 2006) and case studies (Kotler & Lee 2007; Török 2005b).Journal of Economic Literature (JEL) code: D64, M14, L31